Visible particles in parenteral drug products: A review of current safety assessment practice - Frank Liu; Richard Hutchinson (Current Research in Toxicology)
Parenteral drug products (PDPs) are administered extensively to treat various diseases. Product quality plays a critical role in ensuring patient safety and product efficacy. One important quality challenge is the contamination of particles in PDPs. Particle presence in PDPs represents potential safety risk to patients. Differential guidance and practice have been in place for visible (VPs) and subvisible particles (SVPs) in PDPs. For SVPs, the amount limits have been harmonized in multiple Pharmacopeias. The pharmaceutical industry follows the guided limits for regulatory and quality compliance. However, for VPs, no such acceptable limit has been set. This results in not only quality but also safety challenges for manufacturers and drug developers in managing and evaluating VPs. It is important to understand the potential safety risk of VPs so these can be weighed against the benefit of the PDPs. To evaluate their potential risk(s), it is necessary to understand their nature, origin, frequency of their occurrence, safety risk, the risk mitigation measures, and the method to evaluate their safety. The current paper reviews the critical literature on these aspects and provides insight into considerations when performing safety assessment and managing the risk(s) for VPs in PDPs.